Arte Digitale: espressione di un valore innovativo ancora da scoprire - Rea, Giorgio (Archeomatica, 2023)
Digitization as the starting point for a new way of expressing museum potential: from 3D for conservation and use, through the blockchain to guarantee traceability and security up to NFTs for fundraising.